Potential therapeutic effects of ibudilast and retinoic acid against cuprizone-induced behavioral and biochemical changes in mouse brain - Alyami, Kholoud A.; Alshahrany, Gadah A.; Al-Otaibi, Kholoud M.; Alam, Mohammad Z.; Alghamdi, Badrah S.; Alsufiani, Hadeil M.; Alshareef, Nouf O.; Alhoraibi, Hanna M.; Alkhodair, Sahar A.; Omar, Ulfat M. (Frontiers in Molecular Neuroscience, 2025)
Ibudilast (IBD) is a new drug that has been released as treatment for multiple sclerosis (MS). Retinoic acid (RA), a metabolite of vitamin A, is known for its pro-regenerative and anti-inflammatory properties, therefore, it has been suggested as a supplementary treatment for MS. The objective of this study is to investigate the therapeutic effects of RA and IBD against cuprizone (CPZ) induced mouse models. Seventy-two Swiss Albino male Mice (SWR/J) were divided into two main groups control (n = 18); normal chow and CPZ (n = 54); 0.25% of CPZ mixed into chow at demyelination stage (first 5 weeks). The following 4 weeks included two stages of remyelination: early remyelination (2 weeks after CPZ discontinuation) and late remyelination (week 9). In the early stage of remyelination, the CPZ group was divided into four subgroups beside daily treatment intraperitoneal injections CPZ (+ve control- no treatment), RA (20 mg/kg), IBD (10 mg/kg), and RA + IBD, with (n = 12/group), while the control group had 12 mice. At the end of each stage 6 mice/ group were sacrificed. Mice response to different treatments was assessed using several locomotor and cognitive behavior tests including open field test, rotarod test, grip strength test, novel object recognition test (NORT) and Y-maze test. The expression levels of several genes MS associated genes Tumer Necrosis Factor- Alpha (TNF- α), Cyclooxygenase-2 (COX-2), Nerve Growth Factor (NGF), Signal transducer and activator of transcription 3 (STAT-3) and Nuclear factor kappa-light-chain-enhancer of activated b-cell (NFKB-P105) in the brain of mice were measured using quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR) analysis. The results demonstrated that RA supplementation helped in alleviating the symptoms of MS induced mice with or without using IBD treatment. This was indicated as an improvement in locomotor activity, motor coordination and muscular strength as well as improving the cognition and memory functions. The mRNA expression pattern of various MS associated genes indicated that the treatments effectively mitigated the detrimental effects of CPZ in mouse brain. The findings of this study indicate that RA supplements could be effectively unitized as adjuvant therapy alongside with IBD for MS treatment.